Study on Economic Plausibility of Electric Vehicle Charging Stations in Nepal - Tiwari, D.D.; Pokharel, G.C. (Kathmandu University Journal of Science, Engineering and Technology, 2021)
Nepal is targeting to produce 15,000 MW of electrical energy by 2030, and there shall be abundant energy in the country. Electric Vehicle (EV) charging stations can play a vital role in the consumption of the electricity generated within the country, and this can be achieved by adequately installing EV charging stations in different regions across the major highways in Nepal so that EVs can access them easily. This study compares petrol and diesel engine vehicles with an EV (Nissan Leaf) on the cost of energy consumption per kilometer to determine the economic prospect of EVs in Nepal. The total number of EV charging stations required was calculated based on the charging requirements (considering a discharge of 65%). The vehicles were compared based on the energy cost incurred per kilometer factor for a range of 20,000 kilometers. Furthermore, the payback period for setting up an EV charging station was determined based on the charging stipulations for the EVs, cost incurred, and the total revenue in a year. Wherever relevant, the data were adopted from other countries due to insufficient data from Nepal. Results suggest that setting up a total of 64 EV charging stations shall yield a peak power demand of 17.5 MW. Additionally, Nissan Leaf (EV in our study) is found to be the best alternative costing 2.4 Nepalese Rupees (NRs) per kilometer compared to that of petrol and diesel engine vehicles with the cost of 11.2 and 8.7 NRs per kilometer respectively. Also, the return on investment for setting up a single charging station has been determined within a payback period of 3 to 4 years. This study is one of its first kind to determine the prospect of EV charging stations in Nepal and could offer valuable information to control fossil fuel import in the future.